The effect of long-term and short-term loading on the flexural behavior of RC beams strengthened with the NSM method - Sima Rostami Aghouy; Javad Sabzi; M. Reza Esfahani (Case Studies in Construction Materials)
This study investigates the impact of long-term and short-term loading on the flexural behavior of reinforced concrete (RC) beams strengthened using the near surface mounted (NSM) method. In this method, two types of matrices—epoxy resin and repair mortar—are used to bond glass fiber reinforced polymer (GFRP) reinforcing bars to the concrete beams. Nine RC beams, each measuring 150 mm in width, 200 mm in height, and 2000 mm in length, were constructed and strengthened using the NSM method. The results indicate that, under long-term loading, mid-span displacement in beams strengthened with GFRP bars and repair mortar is higher than in those strengthened with GFRP bars and epoxy resin. Additionally, short-term loading results show that beams with low and high steel content exhibit lower load-carrying capacity and mid-span displacement when strengthened with GFRP bars and repair mortar compared to those strengthened with GFRP bars and epoxy resin. Furthermore, beams strengthened with GFRP bars and epoxy resin, initially subjected to long-term sustained service loading and then exposed to short-term loading, show that long-term loading does not significantly affect the ultimate load-carrying capacity of beams with low steel content. However, it reduces the load-carrying capacity by 6 % and 13 % in beams with medium and high steel content, respectively.